Assessment of children’s exposure to air pollutants in urban residences during the COVID-19 pandemic - Abdel-Salam, Mahmoud M. M. (Frontiers in Environmental Science, 2022)
Indoor air pollution has been associated with adverse health effects. Sensitive people such as children spend much time at home. It is therefore important to know whether our children breath clean air inside their residences or not. Monitoring of PM10, PM2.5, TVOCs, CO, and CO2 concentrations was conducted for 24 h in 36 urban residences in Alexandria – Egypt, simultaneously outdoors and indoors (living rooms, bedrooms, and kitchens), during the summer season. During the COVID-19 pandemic, children spend 98% of their time at home (49% in living rooms, 47% in bedrooms, and 2% in kitchens). Results indicated that children are particularly exposed to high concentrations of PM10 (85.4 ± 18.7 µg/m3) and PM2.5 (57.2 ± 16.4 µg/m3) exceeding the WHO guidelines, which can be dangerous for their health. Outdoor sources were found to be a main contributor to the indoor levels of PM10, PM2.5, and CO in bedrooms and living rooms of the surveyed residences. Therefore, effective control measures to reduce outdoor air pollution can result in improved indoor air quality (IAQ). Living rooms showed the highest impact on the daily average children exposure to PM2.5, PM10, TVOCs, and CO with average contributions of 59%, 56%, 57%, and 61%, respectively. For CO2, bedrooms showed the largest contribution to the children’s average exposure with an average value of 49%, pointing to inadequate ventilation and small size of this type of room. Indoor occupants’ activities were found to considerably affect IAQ in the bedrooms and living rooms. The study also highlighted the importance of other determinants, such as occupancy and air exchange rate, on IAQ in these two microenvironments. This research provides the first data on children’s exposure to indoor air pollutants in urban residences in Egypt.